OP0267 INACTIVATED INFLUENZA VACCINATION DOES NOT ASSOCIATE WITH DISEASE FLARES IN AUTOIMMUNE RHEUMATIC DISEASES: A SELF-CONTROLLED CASE SERIES STUDY USING DATA FROM THE CLINICAL PRACTICE RESEARCH DATALINK. (June 2019) - Nakafero, Georgina; Grainge, Matthew; Myles, Puja; Mallen, Christian; Zhang, Weiya; Doherty, Michael; Nguyen-van-Tam, Jonathan; Abhishek, Abhishek
Abstract : Background: Concerns about vaccination with the seasonal flu vaccine associating with increased risk of autoimmune rheumatic disease (AIRD) activity, and anecdotal reports of the seasonal flu vaccine triggering diseases such as vasculitis are barriers to flu vaccination in this population 1-2 . This is despite reports of stable disease activity following flu vaccination provided disease modifying anti-rheumatic drug therapy is continued in the peri-vaccination period 3 . Previous studies generally include patients with stable disease activity, and as far as we are aware, a real world study evaluating the association between inactivated influenza vaccine (IIV) administration and AIRD activity has not been conducted. Objectives: To examine the association between IIV administration and primary care consultation for joint pain, fatigue, rheumatoid arthritis (RA) flare, corticosteroid prescription, and incident vasculitis in people with AIRDs. Methods: We undertook within-person comparisons using self-controlled case-series (SCCS). AIRD cases who received IIV and had an outcome of interest in the same influenza cycle, between 1 st September of one year and 31 st August of the next year, between 2006 and 2016 were ascertained within the Clinical Practice Research Datalink. The influenza cycle (1 st September of one year to 31 st December of the next year) was partitioned into five exposure periods (1-15 days pre-vaccination, and 0-14, 15-30, 31-60, and 61-90 days post-vaccination), with the remaining time period classified as non-exposed. Incidence rate ratios (IRRs) and 95% confidence intervals (CI) were calculated to compare the frequency of outcomes in different periods. Results: Data for 14, 928 AIRD cases (69% women, 80% with RA) were included. There was no association between IIV administration and primary-care consultation for RA flare, corticosteroid prescription, and vasculitis (Table 1). Vaccination associated with reduced primary-care consultation for joint pain in the 90-day post-vaccination period (IRR (95%CI) 0.91(0.87-0.94)), and fatigue (IRR (95%CI) 0.40(0.22-0.71)) in the 61-90 days post vaccination (Table 1). Conclusion: The administration of IIV was not associated with flare of the underlying AIRD and its association with reduced disease activity warrants further investigation. Nevertheless, these data add to the accumulating evidence to support seasonal influenza vaccination in people with AIRDs. References: [1] Loubet P, et al. Vaccine. 2015; 33(31):3703-8. [2] Birck R, et al. Journal of clinical rheumatology: practical reports on rheumatic & musculoskeletal diseases. 2009; 15(6):289-91. [3] Park JK, et al. Annals of the Rheumatic Diseases. 2018; 77(6):898-904. Disclosure of Interests: Georgina Nakafero: None declared, Matthew Grainge : None declared, Puja Myles Grant/research support from: In my previous role I have worked on a project that was funded via an unrestricted educational grant from Roche. See details including contract: https://www.nottingham.ac.uk/research/groups/healthprotection/projects/pride.aspx, Christian Mallen: None declared, Weiya Zhang Consultant for: Grunenthal for advice on gout management, Speakers bureau: Bioiberica as an invited speaker for EULAR 2016 satellite symposium, Michael Doherty Grant/research support from: AstraZeneca funded the Nottingham Sons of Gout study, Consultant for: Advisory boards on gout for Grunenthal and Mallinckrodt, Jonathan Nguyen-van-tam Grant/research support from: From F. Hoffmann-La Roche. See details: https://www.nottingham.ac.uk/research/groups/healthprotection/projects/pride.aspx, Consultant for: Ad hoc paid consultancy and lecturing for several influenza vaccine manufacturers (Sanofi-Pasteur MSD, Sanofi-Pasteur, GlaxoSmithKline plc (GSK), Baxter AG, Solvay, Novartis) and manufacturers of neuraminidase inhibitors (F. Hoffmann-La Roche: oseltamivir (Tamiflu®) and GSK: zanamivir (Relenza®))., Employee of: A former employee of both SmithKline Beecham plc (now part of GSK), Roche Products Ltd. (UK), and Sanofi-Pasteur MSD, all prior to 2005), Speakers bureau: Ad hoc paid consultancy and lecturing for several influenza vaccine manufacturers (Sanofi-Pasteur MSD, Sanofi-Pasteur, GlaxoSmithKline plc (GSK), Baxter AG, Solvay, Novartis) and manufacturers of neuraminidase inhibitors (F. Hoffmann-La Roche: oseltamivir (Tamiflu®) and GSK: zanamivir (Relenza®))., Abhishek Abhishek Grant/research support from: AstraZeneca and OxfordImmunotech, Grant/research support from: AstraZeneca and Oxford Immunotech, Speakers bureau: Menarini pharmaceuticals, Speakers bureau: Menarini pharmaceuticals